The Change4Life Convenience Store Programme to Increase Retail Access to Fresh Fruit and Vegetables: A Mixed Methods Process Evaluation - Adams, Jean; Halligan, Joel; Burges Watson, Duika; Ryan, Vicky; Penn, Linda; Adamson, Ashley J.; White, Martin (PLOS ONE, 2012)
Background Consumption of fruit and vegetables is important for health, but is often lower than recommended and tends to be socio-economically patterned with lower consumption in more deprived groups. In 2008, the English Department of Health introduced the Change4Life convenience store programme. This aimed to increase retail access to fresh fruit and vegetables in deprived, urban areas by providing existing convenience stores with a range of support and branded point-of-sale materials and equipment. Methods We undertook a mixed-methods study of the Change4Life convenience store programme in the North East of England around two years after initial implementation. Store mapping (n = 87; 100% stores) and systematic in-store observations (n = 74; 85% stores) provided information on intervention fidelity; the variety, purchase price and quality of fresh fruit and vegetables on sale; and purchase price compared to a major supermarket. Ten qualitative interviews with a purposive sample of retailers and other professionals explored experiences of the intervention and provided further insight on quantitative results. Results Intervention stores were primarily located in socio-economically disadvantaged areas. Fidelity, in terms of presence of branded materials and equipment, was low and much was not being used as intended. Fresh fruit and vegetables on sale were of high quality and had a purchase price around 10% more than comparable products at a major supermarket. Interviewees were supportive of the health improvement aim of the intervention. Retailers were appreciative of part-funding for chill cabinets and free point-of-sale materials. The intervention suffered from: poor initial and on-going communication between the intervention delivery team and retailers; poor availability of replacement point-of-sale materials; and failure to cement intended links with health workers and community organisations. Conclusions Overall, intervention fidelity was low and the intervention is unlikely to have had a substantial or long-term effect on customers’ consumption of fruit and vegetables.